2016
DOI: 10.1007/s00210-016-1327-2
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib, a tyrosine kinase inhibitor exhibits protection against acute pancreatitis-induced lung and liver damage in rats

Abstract: This investigation explored the nilotinib action in the management of acute pancreatitis (AP) and AP-induced lung and liver injury. AP was induced in Sprague Dawley (SD) rats with L-arginine. Treatment with nilotinib with or without L-arginine was applied for 7 days. Marked deterioration in serum amylase, lipase, aspartate amino transferase (AST), alanine amino transferase (ALT), lactate dehydrogenase (LDH), nitric oxide (NO), total protein content, and transforming growth factor beta1 (TGF-β1) along with panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Other previous studies have shown similar findings. [60][61][62] Previous studies have shown that neutrophils and leukocytes were attracted to the site of injury as early as 3 hours after induction of pancreatitis. Infiltrating polymorphonuclear neutrophils produce oxygen-free radicals and thus cause local and systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies have shown similar findings. [60][61][62] Previous studies have shown that neutrophils and leukocytes were attracted to the site of injury as early as 3 hours after induction of pancreatitis. Infiltrating polymorphonuclear neutrophils produce oxygen-free radicals and thus cause local and systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human soluble thrombomodulin and prostaglandin E1 reduce liver and pancreas damage by maintaining the microcirculation, which improves the prognosis of SAP[ 85 , 86 ]. Nilotinib reduces pancreatic and liver damage through antioxidant and anti-inflammatory effects[ 87 ]. Heme oxygenase-1 can prevent pancreatic and liver damage through antioxidation, the maintenance of the microcirculation, and anti-inflammatory mechanisms[ 88 ].…”
Section: The Clinical Management Of Liaapmentioning
confidence: 99%